The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2022
DOI: 10.3389/fmed.2022.905174
|View full text |Cite
|
Sign up to set email alerts
|

Episiotomy Practice and Its Associated Factors in Africa: A Systematic Review and Meta-Analysis

Abstract: BackgroundEpisiotomy, a surgical procedure that enlarges the vaginal opening during childbirth, was common practice until the early 2000s. Other sources, including the World Health Organization (WHO), advocate for the selective use of episiotomy. Episiotomy rates, on the other hand, have remained high in developing countries, while declining in developed countries. As a result, the current study sought to determine the overall prevalence of episiotomy in Africa as well as the risk factors associated with its p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 87 publications
(191 reference statements)
1
4
0
Order By: Relevance
“…A multicenter clinical trial conducted in 2019 observed a 10% rate of perineal intactness in multiparous women, emphasizing the need for a restrictive episiotomy approach to childbirth to reduce perineal trauma. These findings were consistent with several studies in which primiparity was identified as one of the main risk factors associated with episiotomy [21][22][23][24][25][26]. In addition, factors such as fetal weight greater than 4000 g and vacuum extraction have been found to be independent risk factors for both second-degree perineal tears and obstetric anal sphincter injury [21].…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…A multicenter clinical trial conducted in 2019 observed a 10% rate of perineal intactness in multiparous women, emphasizing the need for a restrictive episiotomy approach to childbirth to reduce perineal trauma. These findings were consistent with several studies in which primiparity was identified as one of the main risk factors associated with episiotomy [21][22][23][24][25][26]. In addition, factors such as fetal weight greater than 4000 g and vacuum extraction have been found to be independent risk factors for both second-degree perineal tears and obstetric anal sphincter injury [21].…”
Section: Discussionsupporting
confidence: 91%
“…In addition, factors such as fetal weight greater than 4000 g and vacuum extraction have been found to be independent risk factors for both second-degree perineal tears and obstetric anal sphincter injury [21]. Other studies have also identified influential factors for the performance of episiotomy in primiparous women, such as maternal age, maternal body mass index, presence of analgesia, duration of the second stage, estimated birth weight, and perineal stress [22][23][24][25][26]. These findings led us to ask what characteristics are determinant for a higher rate of episiotomy in primiparous women and whether these characteristics justify the difference in numbers compared to multiparous women.…”
Section: Discussionmentioning
confidence: 99%
“…This aligns with a 2014 Spanish study, which found an average episiotomy rate of 34.9% among midwives (Hernández‐Martínez et al., 2014 ). These figures are lower than those estimated in developing countries, where they can exceed 40% (Woldegeorgis et al., 2022 ). However, they surpass the rates reported in Western countries, which are documented at 19% (Goueslard et al., 2018 ), 10% (Leclercq et al., 2024 ), and even as low as 2% (Dillon et al., 2021 ).…”
Section: Discussionmentioning
confidence: 57%
“…where they can exceed 40% (Woldegeorgis et al, 2022). However, they surpass the rates reported in Western countries, which are documented at 19% (Goueslard et al, 2018), 10% (Leclercq et al, 2024), and even as low as 2% (Dillon et al, 2021).…”
Section: Episiotomymentioning
confidence: 71%
“…Our finding was congruent with a systematic review and meta-analysis report by Woldegeorgis et al . [ 78 ] that described operative vaginal delivery as a significant contributor to trauma to both the mother and newborn. Moreover, comparative studies in California and Quebec [ 79 ], the Cochrane Database of systematic review [ 80 ], a study in China [ 16 ], Bulgaria [ 81 ], and a retrospective review of operative delivery, in Singapore [ 82 ] identified that forceps or vacuum-assisted vaginal delivery was associated with increased risk of neonatal birth trauma although the risks are generally instrument specific and also affected by correct application and delivery technique as well as complex procedures.…”
Section: Discussionmentioning
confidence: 99%